GIS Application for Modelling Erosion Hazard in Batam Island - Luthfiya Ratnasari; Fara Nabila Rossa (Politeknik Negeri Batam, 2022)
Soil erosion disaster is a disaster that occurs simultaneously with landslide events that occur due to the destruction of the soil layer which then causes erosion followed by landslides. The phenomenon of land erosion occurs due to high rainfall, the influence of slopes and slope length, as well as due to development resources according to Mamarodia (2014). Erosion can also occur due to land degradation, namely the loss of organic matter and nutrients from the root area, this study aims to determine the erosion hazard model in Batam Island which can be displayed in the form of a RUSLE model by utilizing a geographic information system (GIS). The data used in the form of slope maps, land use maps, maps of soil types and rainfall maps on Batam Island using the data processing method used is the RUSLE method to provide information in the form of erosion hazard categories and produce a two-dimensional erosion hazard model map. The result is a map of the erosion hazard model in a two-dimensional form with categories obtained from the combination of the four maps that have been classified. The results of this research are information on the area of ​​soil erosion with very light categories (24,200.42 Ha), light (5,488, 20 Ha), medium (5,100.42 Ha), heavy (3,029.43 Ha), and very heavy (2,929.64 ha) spread over Batam Island. The slope with the highest slope height is class 129,284 ft to 148,627 ft, and the lowest height elevation is in class -6,11 ft to 13,232 ft. the Batam area tends to have an area with an elevation of 13,232 ft to an altitude of 32,574 ft.